Efficacy of intradiscal ozone gas therapy combined with physical therapy in contained lumber disc prolapse (Bangladesh Medical Journal, 2016)
Percutaneous intra-discal ozone therapy has promising results in contained lumber disc prolapse but the effectiveness of this treatment has been tested in large clinical studies show a positive outcome in 70%80% of patients. To increase success rate of ozone discectomy and prevention of disc surgery, intradiscal ozone therapy combined with physical therapy may bring new options for the management of low back pain (LBP) due to lumber disc prolpase. This prospective experimental study was done from August 2014 to Octber 2014 at the Popular Medical College Hospital, Dhanmondi, Dhaka, Bangladesh with the intention to assess the efficacy of percutaneous intra-discal ozone therapy combined with physical therapy in acute and chronic low back pain due to contained prolapsed intervertebral lumber disc (PLID). Seven (7) ml of oxygen-ozone mixture at a concentration of 30 mc/ml was injected in the disc by ozone resistant syringe over a period of 15-20 seconds. All patients got physiotherapy for 30 minutes, two times/day, up to two weeks and strictly maintained activities of daily living (ADL). The main outcome variable was VAS(Visual Analogue Scale) & ODI (Oswestry Disability Index). 100% patient experienced radiation of pain in the leg before ozone gas & physical therapy and 90% had relieved radiation till 4th week. The reduction of VAS score from baseline to four weeks following treatment was 8.0±1.63 to 0.30±0.95. Reduction of Oswestry Disability Index (ODI) from baseline to four weeks following treatment was 37.7±6.5 to 15.8±1.0. Percutaneous intra-discal ozone therapy in combination with physical therapy is an effective treatment for management of low back pain (LBP) due to contained lumber disc prolpase.Bangladesh Med J. 2015 Sep; 44 (3): 146-151